THE EFFECTIVENESS OF GROUP TUTORING SERVICES WITH ART THERAPY TECHNIQUES TO REDUCE NARCISSISTIC BEHAVIOR IN STUDENTS - Sufina Dewi; Saiful Akhyar Lubis (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to determine the effectiveness of group counseling services using art therapy techniques in reducing narcissistic behavior among students. The approach employed is a quantitative method with an experimental research design, specifically a One-Group Pretest-Posttest Design. The research subjects consisted of 21 tenth-grade students (Class X-1) at MAPN 4 Medan who were identified as having high levels of narcissism based on the Narcissistic Personality Inventory (NPI-16) questionnaire. Data analysis techniques included normality test, homogeneity test, and the Wilcoxon Signed Ranks Test. The results of the normality test indicated that the data were not normally distributed (Sig. < 0.05), thus, non-parametric testing was applied. The homogeneity test showed that the variances of pretest and posttest data were homogeneous (Sig. > 0.05). The Wilcoxon test results revealed a significance value of 0.000 (p < 0.05), with all participants scoring lower on the posttest than the pretest, indicating a significant reduction in narcissistic behavior after the intervention. Therefore, group counseling services using art therapy techniques proved to be effective in reducing narcissistic behavior among students.